Novel destabilizing Dynactin variant (DCTN1 p.Tyr78His) in patient with Perry syndrome. (August 2020) - Čierny, Marek; Hooshmand, Sam I; Fee, Dominic; Tripathi, Swarnendu; Dsouza, Nikita R.; La Pean Kirschner, Alison; Zimmermann, Michael T.; Brennan, Ryan
Abstract: Introduction: Perry syndrome, also recognized as Perry disease, is a rare autosomal dominant disorder characterized by midlife-onset atypical parkinsonism, apathy or depression, respiratory failure and weight loss caused by a mutation in the Dynactin ( DCTN1 ) gene. Case description: A fifty-six years-old adopted male presented with atypical parkinsonism with bradykinesia and postural instability, apathy, weight loss, and recurrent respiratory failure due to central hypoventilation requiring tracheostomy. Methods and results: Clinical workup revealed a novel DCTN1 p.Tyr78His variant. Using bioinformatic protein structure modeling, we compare our patient's variant to known DCTN1 mutations and predict protein stability of each variant at the CAP-Gly domain of p150 Glued . All eight variants causing Perry syndrome, as well as Tyr78His, are located at site expected to interact with MAPRE1 tail and are predicted to be destabilizing. Variants causing atypical parkinsonism with incomplete Perry syndrome phenotype (K56R and K68E) are not significantly destabilizing in silico . Conclusion: We propose p.Tyr78His as the ninth pathogenic DCTN1 variant causing Perry syndrome. Bioinformatic protein modeling may provide additional window to understand and interpret DCTN1 variants, as we observed non-destabilizing variants to have different phenotype than destabilizing variants. Highlights: Atypical parkinsonism, depression, apnea, weight loss are caused by DCTN1 mutations. We describe a symptomatic patient with a novel destabilizing Tyr78His DCTN1 variant. DCTN1 variants causing Perry syndrome destabilize p150 Glued at its MAPRE1 interface. Non-destabilizing variants in p150 Glued CAP-Gly domain cause atypical parkinsonism.